Writing California, 1848-1915 - Sikand-Youngs, Nathaniel Rajinder (2024)
In the formative era of its rule by the United States, which spans from the start of the gold rush in 1848 to the dawn of Hollywood in the mid-1910s, California took shape through the written text. There was no inherent rationale for making a single state out of such a vast, disparate section of annexed Mexican land. It fell therefore to literary publications—the foremost mode of cultural production in the long nineteenth century—to find a coherence, even a meaning, to the new otherwise baseless American jurisdiction. By surveying those ways of writing California, this new literary history dispels the myth-and-symbol approach and even the affirmations of exceptionalism that currently define the field. The study begins with the firsthand memoirs of the gold rush, where the new state appears simply as a reflection of the individual authorial experience, before then turning to the rise of regional magazines from the mid-1850s to late 1870s. In those periodicals, California becomes for the first time not just a narrative setting but a literary subject unto itself, one defined by the interplay of its distinctive regional identity with its looming assimilation into a cohesive national whole. After the Civil War, however, scientific surveyors employed by the federal government inverted that paradigm. Their writings insist that the nation must adapt to the local conditions of the far west. This departure from nation-centric approaches to California anticipated the reformist literature of the Gilded Age: naturalist novelists portray California as a semi-organic machine of displacement and exploitation, while environmentalist writers presented its natural wilderness as a valuable economy in itself. The project concludes with the utopian literature of the mid-1910s, which constitutes an idealised future California through the visual relations of seeing and spectacle.